Mitochondrial Quality Control Proteases in Neuronal Welfare - Levytskyy, Roman M. (J Neuroimmune Pharmacol, 2016)
The functional integrity of mitochondria is a critical determinant of neuronal health and compromised mitochondrial function is a commonly recognized factor that underlies a plethora of neurological and neurodegenerative diseases. Metabolic demands of neural cells require high bioenergetic outputs that are often associated with enhanced production of reactive oxygen species. Unopposed accumulation of these respiratory byproducts over time leads to oxidative damage and imbalanced protein homeostasis within mitochondrial subcompartments, which in turn may result in cellular demise. The post-mitotic nature of neurons and their vulnerability to these stress factors necessitate strict protein homeostatic control to prevent such scenarios. A series of evolutionarily conserved proteases is one of the central elements of mitochondrial quality control. These versatile proteolytic enzymes conduct a multitude of activities to preserve normal mitochondrial function during organelle biogenesis, metabolic remodeling and stress. In this review we discuss neuroprotective aspects of mitochondrial quality control proteases and neuropathological manifestations arising from defective proteolysis within the mitochondrion.